Continuous Hydrolysis of Nile Tilapia Skin Collagen using an Enzymatic Membrane Reactor (Journal of Applied Membrane Science & Technology, 2024)
The continuous enzymatic membrane reactor (EMR) was developed for producing Angiotensin-I Converting Enzyme (ACE) inhibitory peptides from Nile tilapia skin collagen. The productive condition of EMR and peptide property were studied. The results showed that protein conversion and EMR capacity were remarkably affected by collagen concentration and enzyme to substrate ratio while ACE-inhibitory activity was influenced by only enzyme to substrate ratio. In addition, the proper operating condition of ACE-Inhibitory peptides produced by EMR were Alcalase to substrate concentration ratio of 0.08 at 50 °C, pH 8.0 and permeate flow rate of 0.4 ml min-1. It was evident that the EMR was an effective means for producing small peptides (< 1000 Da) with ACE-inhibitory activity. The permeate fractions containing peptides with molecular weight
Keywords: Enzymatic membrane reactor, Nile tilapia, fish-skin collagen, peptides, ACE-inhibitory activity